Differential Expression of Decorin in Metastasising Colorectal Carcinoma Is Regulated by miR-200c and Long Non-Coding RNAs - Margareta Žlajpah; Kristian Urh; Jan Grosek; Nina Zidar; Emanuela Boštjančič (Biomedicines, 2022)
Decorin (DCN) is one of the matricellular proteins that participate in normal cells’ function as well as in cancerogenesis. While its expression in primary tumours is well known, there is limited data about its expression in metastases. Furthermore, the post-transcriptional regulation of DCN is still questionable, although it is well accepted that it is an important mechanism of developing metastatic cancer. The aim of our study was to analyse the expression of DCN and its potential regulatory ncRNAs in metastatic colorectal carcinoma (CRC). Nineteen patients with metastatic CRC were included. Using qPCR, we analysed the expression of DCN, miR-200c and five lncRNAs (LUCAT1, MALAT1, lncTCF7, XIST, and ZFAS1) in lymph node and liver metastases in comparison to the invasive front and central part of a primary tumour. Our results showed insignificant upregulation of DCN and significant upregulation for miR-200c, MALAT1, lncTCF7 and ZFAS1 in metastases compared to the primary tumour. miR-200c showed a positive correlation with DCN, and the aforementioned lncRNAs exhibited a significant positive correlation with miR-200c expression in metastatic CRC. Our results suggest that DCN as well as miR-200c, MALAT1, lncTCF7 and ZFAS1 contribute to the development of metastases in CRC and that regulation of DCN expression in CRC by ncRNAs is accomplished in an indirect manner.